Knowledge about aerosol injection does not reduce individual mitigation efforts - Merk, Christine; Pönitzsch, Gert; Rehdanz, Katrin (Environmental research letters, 2016)
Stratospheric aerosol injection (SAI) is a climate engineering method that is reputed to be very effective in cooling the planet but is also thought to involve major risks and side effects. As a new option in the bid to counter climate change, it has attracted an increasing amount of research and the debate on its potential gained momentum after it was referred to in the 5th IPCC assessment report (IPCC 2013). One major objection to SAI and the research done on it is that it could undermine commitment to the mitigation of greenhouse gases. Policymakers, interest groups or individuals might wrongly perceive SAI as an easy fix for climate change and accordingly reduce their mitigation efforts. This is the first study to provide an empirical evaluation of this claim for individuals. In a large-scale framed field experiment with more than 650 participants, we provide evidence that people do not back-pedal on mitigation when they are told that the climate change problem could be partly addressed via SAI. Instead, we observe that people who have been informed about SAI mitigate more than people who have not. Our data suggest that the increase is driven by a perception of SAI as potential threat.